Analysis of Physical Fitness Level Elementary School Students during the Covid-19 Pandemic (ASEAN Journal of Science and Engineering Education, 2023)
The Covid-19 Pandemic period brought many behavioral changes in humans, one of which was in maintaining physical fitness because of the many limitations and government regulations that required staying at home. Physical fitness is one of the things that must be considered because physical fitness can increase body immunity and reduce the risk of being exposed to COVID-19. This study aims to determine the level of physical fitness in elementary school students. This research is a descriptive research and the method used is using test and measurement techniques. The instrument used to measure physical fitness is the Indonesian Physical Fitness Test (TKJI) for children aged 10-12 years. The population of this research is the sixth grade elementary school students, and the samples taken are 15 male students. The results obtained in this study are very good classification 0.0% (0 students), good 6.7% (1 student), moderate 53.3% (8 students), less 40.0% (6 students) and very less 0.0% (0 students). It can be concluded that the average level of physical fitness of students at Elementary Schools during the covid-19 pandemic can be categorized as moderate.